Well-being as a Category (Non)Present in the Teacher’s Line of Thinking About Student’s Success - Baran, Jolanta; Baraniewicz, Danuta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Striving for a success in parallel to the simultaneous attainment of high level of well-being is these days a common phenomenon. For quite a long time it has been also in the focus of the scientific debates and papers also dealing with education. This paper presents the findings of the study on the teachers’ perception of the student success in the context of assessment of selected success determinants and/or indicators. While analysing the theoretical relationship between student's well-being and educational success, 4 selected factors taken from the Buchner (2004) study were considered key to the undertaken research. The results showed that teachers tend to recognize factors related to the student's well-being as indicators of success, which means they perceive it as a result of achievement. Meanwhile the care for the student’s well-being before undertaking an educational task as a success determinant-related situation seems to be less visible.